Teks Hedung Identitas Budaya Masyarakat Leworahang Kabupaten Flores Timur - Henakin, Stefanus Tebajak; Demon, Yosef; Kelen, Theresia Kutun (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to obtain an overview of the form, meaning, and function of the hedung text in the Leworahang community, East Flores district. The approach used in this study is a qualitative approach. Data was collected using the interview, note-taking, and documentation methods. The theory used in this research is cultural linguistic theory. The result of this study indicate that the form, meaning, and function of the hedung text in the Leworahang community, East Flores district have (1) grammatical aspects: reference (reference) namely persona and demonstrative reference; (2) lexical aspects, namely synonyms (equivalents) and antonyms (opposite word). Religious meaning and the meaning of respect for ancestors. Cultural function and social function.